Modulation of the Activities of Neuronal Ion Channels by Fatty Acid-Derived Pro-Resolvents - Choi, Geunyeol; Hwang, Sun Wook (Frontiers in Physiology, 2016)
Progress of inflammation depends on the balance between two biological mechanisms: pro-inflammatory and pro-resolving processes. Many extracellular and intracellular molecular components including cytokines, growth factors, steroids, neurotransmitters, and lipidergic mediators and their receptors contribute to the two processes, generated from cellular participants during inflammation. Fatty acid-derived mediators are crucial in directing the inflammatory phase and orchestrating heterogeneous reactions of participants such as inflamed cells, innate immune cells, vascular components, innervating neurons, etc. As well as activating specific types of receptor molecules, lipidergic mediators can actively control the functions of various ion channels via direct binding and/or signal transduction, thereby altering cellular functions. Lipid mediators can be divided into two classes based on which of the two processes they promote: pro-inflammatory, which includes prostaglandins and leukotrienes, and pro-resolving, which includes lipoxins, resolvins, and maresins. The research on the modulations of neuronal ion channels regarding the actions of the pro-inflammatory class has begun relatively earlier while the focus is currently expanding to cover the ion channel interaction with pro-resolvents. As a result, knowledge of inhibitory mechanisms by the pro-resolvents, historically seldom found for other known endogenous modulators or pro-inflammatory mediators, is accumulating particularly upon sensory neuronal cation channels. Diverse mechanistic explanations at molecular levels are being proposed and refined. Here we overviewed the interactions of lipidergic pro-resolvents with neuronal ion channels and outcomes from the interactions, focusing on transient receptor potential (TRP) ion channels. We also discuss unanswered hypotheses and perspectives regarding their interactions.